Penyelesaian Sengketa Administrasi dalam Pengadaan Barang/ Jasa Pemerintah di Kota Batam - Ningrum, Intan Sari Widya (Universitas Internasional Batam, 2016)
Batam City has 70 government institutions, that consists of the regional and central government. The government goods/ service need to be done in order to improve public service. Indonesia implements the Presidential Decree Number 70 of 2012 on the Second Amendment of Presidential Decree Number 54 of 2010 on the Government Goods/ Service Procurement. Article 81 & 82 of Presidential Decree Number 70 of 2012 state that participants who feel aggrieved may submit their complaints and the complaints may be appealed. The word ?may? in Article 81 and 82 of Presidential Decree Number 70 of 2012 obscures the obligation to use administrative efforts (complaints) in Article 48 of Law Number 5 of 1986 on Administrative Court. Reviewing the administrative dispute resolution arrangements in the procurement of government goods/ services, examining the implementation of administrative dispute resolution through administrative effort and through the court, and finding the ideal socialization concept and the rule of law in the administrative dispute resolution procurement of governmant goods / services in Batam city were the purposes of this research. Normative legal research used as the research method. The results showed that the word ?can? in article 81 and 82 this presidential decree obscures the interpretation of those who seek for justice and it is right for the procurement of government goods/ services to be based upon as the product of law. The application of procurement service is not yet perfect. Therefore, a seriousness from those who seek for justice in filing a lawsuit in court is needed, and stages of litigation in administrative courts should be able to minimize the desicion of which is not acceptable (niet onvankelijkverklaard). A certification for the government goods/ service procurement?s judge. To the violation of this law should later be subject to administrative sanction threat, not criminal sanctions. === Kota Batam memiliki 70 institusi pemerintahan yang terdiri atas pemerintahan pusat dan daerah. Untuk meningkatkan kualitas pelayanan publik, maka pemerintah perlu melaksanakan pengadaan barang/ jasa pemerintah. Indonesia menerapkan Peraturan Presiden Nomor 70 Tahun 2012 tentang Pengadaan Barang/Jasa Pemerintah. Pada Pasal 81 dan 82 peraturan presiden ini menyatakan bahwa penyedia barang/ jasa yang merasa dirugikan dapat mengajukan sanggahan dan dapat mengajukan sanggahan banding. Kata dapat di Pasal 81 dan 82 ini mengaburkan kewajiban upaya administratif pada Pasal 48 Undang-Undang Nomor 5 Tahun 1986 tentang Peradilan Tata Usaha Negara. Menelaah pengaturan penyelesaian sengketa administrasi dalam pengadaan barang/ jasa pemerintah, menelaah pelaksanaan penyelesaian sengketa administrasi melalui upaya administratif dan melalui pengadilan, dan menemukan konsep ideal sosialisasi dan aturan hukum penyelesaian sengketa administrasi dalam pengadaan barang/ jasa pemerintah di Kota Batam merupakan tujuan dari penelitian ini. Metode yang dipakai adalah penelitian yuridis normatif. Hasil penelitian menunjukkan bahwa kata ?dapat? pada pasal 81  dan Pasal 82 peraturan presiden ini mengaburkan penafsiran terhadap masyarakat pencari keadilan. Aplikasi Layanan Pengadaan Secara Elektronik belum sepenuhnya sempurna, dituntut keseriusan dari masyarakat pencari keadilan dalam mengajukan gugatan di peradilan, dan tahapan berperkara di peradilan tata usaha negara seharusnya dapat meminimalisir putusan yang tidak diterima (niet onvankelijkverklaard). Perlu sertifikasi bagi hakim pengadaan barang jasa pemerintah, pembentukan produk hukum yang setingkat undang-undang bagi pengadaan barang/ jasa pemerintah, dan terhadap pelanggaran undang-undang ini nantinya dikenakan ancaman sanksi administratif dan bukanlah sanksi pidana.